PRIORITAS MUSTAHIQ ZAKAT MENURUT TEUNGKU MUHAMMAD HASBI ASH SHIDDIEQY - Syahril Jamil (Kopertais Wilayah VII Palembang, 2015)
Humans were given the authority to manage, develop, and enable the property and the universe and its environment for survival. That is, human rights over natural resources and assets available to him is limited to the maintenance, management and utilization alone. And as a mandate of his property should be used in His way. Concrete form is by issuing charity, infak and Sadaqah which must be distributed fairly to those who deserve it. In the perspective of Hasbi, zakat is the most powerful weapons to combat and eradicate indigence and poverty are structural, as well as an element of community development just, prosperous, materially and spiritually prosperous. And eight ashnaf zakat (mustahiq), are: Poor, poor, amyl, muallafah, riqâb, ghârim, Sabilillah fi, and Ibn Sabil, a group of people who should be empowered, both in terms of life and social status with priority homeless and destitute